Islamic Law Perspective on the Use of Incense in Thanksgiving Events at the Balabe Customs in Kailinese Ethnic - Hikwan Wahyudi; Ubay Harun; Muhammad Taufik (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2021)
The traditional Balabe or Nolabe in the thanksgiving event is an asset of cultural wealth in Central Sulawesi, Indonesia. The Balebe or Molabe custom is carried out every time there are celebratory activities such as weddings, mourning, childbirth and others. This study aims to provide knowledge and understanding of the process of using incense in the implementation of the Balabe custom and how to review Islamic law on the tradition. This study uses a qualitative approach, namely research procedures that produce descriptive data in the form of written or spoken words from people related to the people in Palupi, especially the Kaili tribe. The data collection techniques used in this research are observation, interview, and documentation techniques. Furthermore, after the data is collected, the data obtained needs to be analyzed in three stages that run in cycles: data reduction, data presentation, and drawing conclusions or verification. The results of this study indicate that basically, the major schools of jurisprudence agree to accept customs as the basis for the formation of law. However, in terms of numbers and details, there are differences of opinion between these schools, so that 'urf is included in the group of disputed arguments among scholars. The research implies that it is hoped that all leaders, the community and local government officials will maintain and preserve the bolabe tradition in order to survive even in the face of today's times.